Revisiting the Development of Gifted Preschoolers - Kuznetsova I. A. (Psychological and Pedagogical Support of Talented Children: Problems, Directions, Approaches, Conditions, 2020)
the definitions of the concept of "giftedness" and "gifted child" are presented. The main signs of giftedness in preschool age are characterized. The relevance of early detection of children with signs of giftedness is justified. The difficulties that teachers of preschool institutions face when working with this category of children are pointed out. Also, the views of domestic scientists on the genesis of abilities and giftedness are described.
Keywords: одаренность; одаренный ребенок; личностные особенности; признаки одаренности; giftedness; gifted child; концепция одаренности; the concept of giftedness; signs of giftedness; personal characteristics